Preceptee Experience of Preceptorship in Universitas Sumatera Utara Teaching Hospital, Medan, Indonesia - Rika Endah Nurhidayah; Hasmela Revi (Publisher Cv. Inara, 2020)
University of Sumatra Utara Hospital (USU Hospital) is a teaching hospital managed by the university. USU Hospital as a teaching hospital guarantees the delivery of quality services, education and research and prioritizes learning programs for all professions at USU. Teaching hospitals need an ideal clinical learning model that can accommodate the curriculum that students must take. The study design is a qualitative phenomenology with the aim of exploring the perceived experience of implementing preceptor ship at USU hospitals. Research informants consists of 12 students whom are attending professional nursing education. Research data was collected in the process of Focus Group Discussion (FGD). The results found five themes, namely frequency of visits, methods of supervision, achievement of competence, self-confidence, and collaboration.